Midcourse phase guidance of an interceptor: a simplified suboptimal onboard implementation technique - Sankar, Ram B; Tiwari, Pawan Kishore; Annam, Chandrakanth; Bandyopadhyay, Bijnan; Arya, Hemendra (Sadhana (Bangalore), 2025)
This study deals with the midcourse guidance of an interceptor against various highly maneuvering aerial targets. The interceptors of this class generally use solid propellant-based rocket motors to provide energy for the interceptor to reach the designated target in the specified range. The duration of propellant energy availability for such interceptors is generally a smaller fraction of the total interceptor time of flight. Good intercept velocity is necessary for intercepting highly maneuvering targets with adequate latax capability. Optimal guidance design can be carried out for maximizing the intercept velocity using offline simulations, and a lot of research has happened in this area in the past. However, methods for online implementation of such guidance schemes need to be identified. This study explains a new simplified approach toward online implementation of optimal guidance design. The objective of this work is to develop a suboptimal onboard implementable midcourse guidance scheme that meets the objective of maximizing the target intercept velocity. Subsequently, the tracking of guidance variable is performed using a higher-order sliding mode technique. A two-stage higher-order sliding mode-based autopilot is also designed to ascertain the performance of this guidance scheme in a high-fidelity six-degrees-of-freedom (6-DOF) simulation setup.